2001
DOI: 10.1034/j.1398-9995.2001.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of serum‐treated zymosan (STZ)‐induced oxidative metabolism by human eosinophils and the effects of IL‐5 priming

Abstract: STZ-induced oxidative metabolism consists of different stages. The initial stage (t(1/2) rises of the curves) is PkC dependent and MEK independent, while the end stage (maximum radical production) is PkC, MEK, and PI3 kinase dependent. IL-5 shortened the initial stage, and increased the end stage. During allergen exposure, however, the end stage was reduced by IL-5. This could be due to increased amounts of hypodense eosinophils and/or some abnormality in cell responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The present work has shown that superoxide production by equine eosinophils in response to IL-5 of either equine or human origin, like that induced by histamine [12], appears to be dependent on PKC as Ro31-8220 significantly inhibited the response. This agrees with findings in human eosinophils using IL-5 [18] and STZ [19].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The present work has shown that superoxide production by equine eosinophils in response to IL-5 of either equine or human origin, like that induced by histamine [12], appears to be dependent on PKC as Ro31-8220 significantly inhibited the response. This agrees with findings in human eosinophils using IL-5 [18] and STZ [19].…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, conventional PKCs appear to be involved in regulating the adherence of equine eosinophils in response to human IL-5. The concentrations of Gö6976 required for effective inhibition were higher than the IC 50 reported for inhibition in a cell-free system [22], but others have also reported that mM concentrations are necessary to inhibit human eosinophil function [16,19,20]. The inhibitory effects of Gö6976 on equine eosinophil function are also consistent with the report that PKCa is involved in H1 receptor signalling in CHO cells transfected with bovine H1 receptors [27] and with the finding that, in activated cells, PKCb associates with the signal transducing beta chain of the IL-5 receptor [28].…”
Section: Discussionmentioning
confidence: 92%
“…An interesting observation regarding staurosporine was made in a study on eosinophil oxidative metabolism by Woschnagg et al. where this inhibitor had a priming‐like effect on zymosan‐induced oxidative metabolism (10). This phenomenon was not observed when using PMA as an inducer (39).…”
Section: Discussionmentioning
confidence: 99%
“…Several inhibitors have been found to interfere with signal transduction in eosinophils and antagonize the function of these cells. Many of these inhibitors are directed against general signalling molecules in granulocytes including PI3‐kinase (Wortmannin and LY294002), protein kinase C (Staurosporine, Gö6976), protein tyrosine kinases (Genistein) and mitogen‐activated protein kinase (MEK) (PD98059) (10–16).…”
mentioning
confidence: 99%
“…The possibility that IL-2 inhibits PI3-kinase-induced migration was not feasible to investigate by the same approach because of the inhibitory effect of both the PI3-kinase inhibitors and IL-2 on the migration. However, IL-5 is known to induce PI3-kinase activity [18,19,20], and in our previous study the inhibitory effect of IL-2 was counteracted by IL-5 [12]. This may indicate that IL-2 and IL-5 have opposite effects on the PI3-kinase pathway.…”
Section: Discussionmentioning
confidence: 88%